Mussel-inspired construction of superhydrophilic/underwater superoleophobic PTFE membranes using a novel ε-polylysine-based modification for efficient oil-water separation - Xin Wu; Chenyang Li; Shuiling Hong; Ang Gao; Haoming Duan; Wei Li; Shuo Yang; Leixin Yang; Dengkun Shu; Jingwei Xie; Bowen Cheng (Journal of Environmental Chemical Engineering, 2026)

Synergistic TP/APTES coating on PBT membrane enables superhydrophilicity and efficient oil-water separation - Shuiling Hong; Chenyang Li; Xin Wu; Ang Gao; Haoming Duan; Man Liu; Sijia Zhang; Shuo Yang; Leixin Yang; Dengkun Shu; Jingwei Xie; Bowen Cheng (Journal of Environmental Chemical Engineering, 2026)

Structurally decoupled strongly hydrophobic biocathode enables high-performance flexible enzymatic biofuel cells for self-powered sensing - Jie Gao; Ang Xu; Jia Wu; Jinlong He; Ping Wang; Ying Liu; Qiang Wang; Bo Xu; Yuanyuan Yu; Man Zhou (Chemical Engineering Journal, 2026)

Multi-objective optimization for multi-zone HVAC system via physics-integrated predictive control framework with CFD-assisted visualization - Fangli Hou; Jack C.P. Cheng; Cong Huang; Ang Li; Helen H.L. Kwok; Zhaoji Wu (Building and Environment, 2026)

Hydrodynamic interference and load evolution of staggered cylinder pairs under dam-break waves: An active learning-based Kriging modeling framework - Zhengjie Wu; Ang Liu; Yong Xu; Zexing Jiang; Bingling Wang; Yuanmin Zhao; Guoji Xu (Ocean Engineering, 2026)

Coupled molybdenum and iron isotopes distinguish seawater and hydrothermal inputs to seep carbonates - Hangyu Nan; Xiaoming Miao; Hongxiang Guan; Ang Li; Zhilei Sun; Thomas J. Algeo; Davide Oppo; Nengyou Wu; Sanzhong Li (Geochimica et Cosmochimica Acta, 2026)

Activating lattice oxygen in Ni-doped SnO2 to break surface confinement for high-performance hydrogen sensing - Meili Wu; Yanbai Shen; Sikai Zhao; Ang Li; Jinzhou Bai; Qiang Zhao; Wenbao Liu; Zhenyu Yuan; Fanli Meng (Chemical Engineering Journal, 2026)

Cajaninstilbene acid induced apoptosis and cell cycle arrest in glioblastoma multiforme through mitochondrial ROS–mediated MAPK pathways - Yong-Ang Li; Tian-Zeng Bian; Hong Li; Jia-Wen Li; Liu-Tao Ma; Hao-Di Wu; Shuai Chen; Jia-Yi Chen; Hao Zeng; You-Bing Mao; Peng Wang; Qi Qiao (Food and Chemical Toxicology, 2026)

Field-measured PM2.5 and chemical emission characteristics from non-road construction equipment (NRCE) in China: Multi-factor insights - Bobo Wu; Ang Zhang; Zichun Wu; Zhiliang Yao; Luyang Miao; Peng Wu; Xianbao Shen (Atmospheric Pollution Research, 2026)

Surface-engineered Mn–Prussian Blue analogue with dual redox centers for high-performance hybrid capacitive deionization - Jianeng Ji; Jun Yang; Zhiqiang Wu; He Ren; Hao Fu; Chunyan Li; Minjie Shi; Edison Huixiang Ang (Chemical Engineering Journal, 2026)

Physical exercise protects cardiovascular fitness in long-term spaceflight: what have we learned? - Zi’ang Zhang; Wenjuan Xing; Guiling Wu; Xing Zhang; Jia Li; Yingxian Li; Feng Gao (Science China Life Sciences, 2026)

Contrasting responses to environmental stresses for macroinvertebrates and benthic algae in subtropic Qinhuai rivers - Lei Han; Ming Chen; Song Bai; Ang Hu; Peixuan Zhang; Beryl Ochieng; Yifan Cui; Jinfu Liu; Shaojuan Du; Hao Wu; Xiefa Song; Kang Song; et al. (Journal of Hydrology, 2026)

Topography‐Mediated Soil Moisture Controls Forest Hillslope‐Scale NO and N 2 O Emissions - Kai Huang; Dongwei Liu; Yihang Duan; Di Wu; Geshere Abdisa Gurmesa; Ronghua Kang; Jingwen Xu; Xue Li; Yuqi Liu; Erik A. Hobbie; Xiaoming Fang; Chenxia Su; et al. (Global Change Biology, 2026)
Temperate forests are key terrestrial carbon sinks, yet their capacity to sequester carbon is often limited by nitrogen (N), a nutrient whose availability is declining in many ecosystems. Among factors contributing to declining N availability, climate‐driven changes in soil hydrology could force N loss via the emission of both nitric oxide (NO) and nitrous oxide (N 2 O); however, forecasting these losses is challenging because they are regulated by soil moisture, a factor that regulates microbial activity and substrate availability but varies significantly across space and time. Here, we ask: how do topography‐driven soil moisture gradients and changes in seasonality (e.g., spring–thaw cycles) mediate hillslope‐scale N emissions? We measured over 2 years of high‐resolution in situ NO and N 2 O fluxes from 16 automated chambers deployed along a topographic gradient in a temperate forest to show that soil moisture gradients governed spatial and temporal patterns of soil N emissions. These gradients produced tradeoffs in process controls, whereby temperature regulated N emissions in drier upper positions, giving way to soil moisture regulating microbial pathways and emissions in wetter downslope positions. We then used these relationships among soil moisture, temperature, and N availability to develop models for predicting hillslope‐scale NO + N 2 O losses. Annual emissions averaged 0.2 kg NO‐N ha −1 (range: 0.1–0.3) and 1.0 kg N 2 O‐N ha −1 (range: 0.7–4.9), with N 2 O showing a stronger response to moisture‐driven changes than NO. The spring freeze–thaw period accounted for 15%–26% of NO and 24%–58% of N 2 O annual emissions, with the highest emissions measured consistently at lower topographic positions. These findings establish topography‐mediated hydrology as a primary control of forest soil N dynamics and gaseous N emissions, reducing uncertainty in forecasts of hillslope‐scale N losses under a changing climate.

Dynamic Response and Operational Performance of an Integrated Floating Wind Turbine–Net Cage Platform - Xing-Hua Shi; Qiang Ang; Jing Zhang; Honglong Li; Chunhan Wu; Shan Wang (Journal of Marine Science and Engineering, 2026)
This study investigates the floating wind turbine (FWT)–Net cage integrated platform, where the net cage is rigidly connected to the FWT foundation. The platform is numerically modeled using time-domain simulations in OrcaFlex V11.1, based on representative environmental conditions of the South China Sea. The operational performance of two layouts of the platform is evaluated and compared, considering both power generation efficiency and residual volume ratio as key indicators. The results show that the FWT–Net cage integrated platform exhibits superior hydrodynamic stability, characterized by reduced surge and pitch motions, lower mooring force fluctuations, and a higher residual cage volume. Additionally, the platform achieves better power generation efficiency and a higher residual volume ratio, indicating more effective use of the aquaculture space. Based on these findings, an improved integrated design incorporating additional outer net cages is proposed. This design demonstrates enhanced aquaculture capacity while maintaining power generation. The results provide valuable insights for the design of FWT–Net cage integration, promoting the efficient and sustainable utilization of marine space.

Double-defect ZnO aerogel-supported single-atomic ruthenium for selective gas-solid phasephotooxidation of methane to methanol - Xiaochao Xu; Xiangxia Wu; Zhen Xiao; Zhi-Ang Zhao; Guanwei Peng; Jinni Shen; Lifang Yang; Wenxin Dai; Zizhong Zhang (Chemical Engineering Journal, 2026)

Captive breeding and early development of tank-reared lyretail anthias Pseudanthias squamipinnis (Peters, 1855): Assessments of hatching success, larval survival, and ontogeny - Ting-Chan Chou; Ang Lu; Yi-Yang Lin; Cheng-Chieh Wu; Hei-Wan Wong; Ho-Fai Yik; Bo-Kai Liao; Hong-Yi Gong; Yen-Ju Pan (Aquaculture, 2026)

Corrigendum to “Mechanisms, pathological features, and intervention strategies for nitrogen mustard-induced skin toxicity” [Toxicol. Lett. 416 (2026) 111815] - Bing Zhu; Guanchao Mao; Qinghe Meng; Ang Li; Chaoying Jin; Yuchong Wang; Xinwei Wang; Wenjun Xue; Fangzhen Hou; Junjie Yang; Qingqiang Xu; Chunyu Xue; et al. (Toxicology Letters, 2026)

Mechanisms, pathological features, and intervention strategies for nitrogen mustard-induced skin toxicity - Bing Zhu; Guanchao Mao; Qinghe Meng; Ang Li; Chaoying Jin; Yuchong Wang; Xinwei Wang; Wenjun Xue; Fangzhen Hou; Junjie Yang; Qingqiang Xu; Chunyu Xue; et al. (Toxicology Letters, 2026)

Superoxide mediated Mn(II) oxidation of an alkali-tolerant bacterium Pseudorhizobium flavum MXJ-1 - Haixia Pan; Fei Li; Ruiying Zhang; Yu Liu; Jieyi Li; Tongtong Wu; Ang Li; Hao Zhou (Journal of Environmental Sciences, 2026)

Gliding arc plasma-driven ammonia decomposition for pure ammonia spark-ignition engine - Yezeng Fan; Tiankui Zhu; Zhuohang Li; Jinze Li; Peibo Gao; Jing Wu; Zhan Gao; Ang Li; Lei Zhu; Zhen Huang (Fuel, 2026)

Effects of curcumin and Curcuma longa extract on inflammatory biomarkers in patients with rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE): a systematic review and meta-analysis of randomized controlled trials - Ang-Jun Liu; Po-Chang Wu; Yu-Pei Chen; Hsueh-Ting Chu; Hen-Hong Chang (Inflammation Research, 2025)

Carbon sequestration induced by enhanced silicate rock weathering in a temperate larch plantation in Northeastern China - Zhou Wu; Chenxia Su; Meixia Gao; Ronghua Kang; Daniel S. Goll; Meng Yao; Zihan Tai; Ang Wang; Qing-Wei Wang; Yunting Fang (Forest Ecology and Management, 2025)

Acetylated glucomannan-CNT scaffolds with dual-drug release promote hiPSCs-driven cortical regeneration by suppressing inflammation and anoikis - Yue Gao; Wenxi Li; Wanting Lu; Fuqiang Tang; Xian Xiao; Yinggang Li; Jiaxing Huang; Zhiqi Liang; Yuqing Wu; Yanwen Li; Qingjian Zou; Liangxue Lai; et al. (Carbohydrate Polymers, 2025)

A non-invasive continuous glucose monitoring method based on the Bergman minimal model - Ang Li; Long Zhao; Chenyang Wu; Zhanxiao Geng; Lihui Yang; Fei Tang (Medical & Biological Engineering & Computing, 2025)

Impact of Fluid Sloshing on BOG Generation in Type B LNG Tanks During Ship Emergency Stops - Haikang Zhao; Gang Wu; Jiachen Chen; Xigang Pu; Sicong Wang; Yuhao Yuan; Ang Sun (Journal of Marine Science and Engineering, 2025)
The safe and efficient transport of Liquefied Natural Gas (LNG) is critically dependent on understanding fluid dynamics within cargo tanks, which directly influence structural integrity and operational safety. Study employs the Volume of Fluid (VOF) method to simulate fluid sloshing and phase change dynamics in Type B LNG cargo tanks during emergency stop conditions. The transient simulations employ a time step of 5 × 10−3 s, a model with 46,840 grids, and the analysis focuses on impact forces on tank walls, their dependence on filling levels. Results show that the flow disturbance caused by vessel rolling increases BOG generation fluctuations by approximately 35%. Sloshing significantly increases BOG generation, particularly after a 10 s relaxation period, as the initial shock enhances heat transfer and mixing, accelerating vapor production. Original components of LNG are sensitive to BOG generation and impact forces on the front bulkhead are significantly higher than on the rear, with peak impacts occurring. The filling rate is a critical parameter influencing fluid dynamics and safety in LNG transportation. Impact magnitude increases with fill level up while at about 80% it declines; impact timing shortens at higher fill ratios. A BOG generation mechanism in which microscale turbulence and ongoing thermal imbalance govern the kinetics of evaporation phase transitions was proposed. It was discovered that the impact forces and BOG production exhibit rise–fall–rise patterns driven by impact dynamics, condensation, and evaporation processes. The findings highlight the critical role of fluid sloshing in affecting tank safety and operational efficiency, offering insights into designing more resilient LNG cargo tanks and optimizing transportation safety and economy.

Sand encased by fine-grained sediment regulates methane migration through the gas hydrate stability zone - Jiliang Wang; Ang Li; Wei Zhang; Jin Sun; Jiecheng Zhang; Xueqing Zhou; Shiguo Wu (Earth and Planetary Science Letters, 2025)

Unveiling critical drivers of soil salinity prediction accuracy in remote sensing: a global meta-analysis - Zi’ang Cui; Ruiqi Zhang; Wenhui Wang; Zhaoce Peng; Yifan Wu; Ziyue Zhao; Mohan Li; Yutong Cong; Shaoyan Zhang; Zhenhai Li; Lijing Han; Jianli Ding (Plant and Soil, 2025)

Scale-factor-based regional zenith tropospheric delay modeling for real-time precise point positioning - Hao Chen; Ningbo Wang; Zishen Li; Kefei Zhang; Suqin Wu; Peng Sun; Ang Liu; Gongwei Xiao (Advances in Space Research, 2025)

Impact of per- and polyfluoroalkyl substances exposure on renal dysfunction: Integrating epidemiological evidence with mechanistic insights - Weitao Su; Ziwen An; Yayuan Mei; Zhenzhen Tan; Zexuan Jiang; Xiuli Zeng; Zhiqiang Dong; Ming Yang; Jingtao Wu; Huicai Guo; Ang Li (Environmental Pollution, 2025)

Rational design of SnO2 quantum dots/SnS2 hybrids for enhanced NO2 sensing at room temperature: Insights from DFT and in-situ DRIFTS - Jinzhou Bai; Yanbai Shen; Ang Li; Meili Wu; Siyao Liu; Wenbao Liu; Qiang Zhao; Sikai Zhao; Fanli Meng (Chemical Engineering Journal, 2025)

Two new alkamides and a new polyacetylene glucoside from Achillea alpina L. - Ang Li; Xiu-Wei Li; Huan Guo; Qiang Guo; Xia Wu; Xiao-Qing Chen (Phytochemistry Letters, 2025)

Study on short-term total hardness prediction of water quality based on CNN-BiLSTM-SA model: A case study of Henan Province - Huan Xu; Hehu Zhang; Youwei Wang; Lingling Lu; Ang Wu; Ying Chen; Yahui Li; Chuanxin Dong; Xiushan Wang (Journal of Water Process Engineering, 2025)

Intelligent real-time status identification for anti-roll tank via solid-liquid triboelectric nanogenerators - Xing'ang Xu; Hao Wu; Zhongjie Li; Siyu Jia; Shuaitao Jin (Ocean Engineering, 2025)

Dynamic interactions between Fe, Mn, S and C cycles in the Okinawa Trough seep sediments - Cuiling Xu; Qing Li; Taiheng Lv; Zhilei Sun; Ang Li; Ye Chen; Xilin Zhang; Feng Cai; Nengyou Wu (Global and Planetary Change, 2025)

60Co-γ-ray-irradiated edible silkworm (Bombyx mori) pupae-assisted protease digestion: A strategy for obtaining low molecular weight bioactive peptides - Xiao-Meng Xun; Cheng-Hai Yan; Zi-Xuan Yuan; Zhi-Ang Zhang; Richard Ansah Herman; Yan Xu; Qiong-Ying Wu; Jun Wang (Sustainable Chemistry and Pharmacy, 2025)

Hydroxylation of dihydromyricetin via Beauveria bassiana fermentation enhances its efficacy in improving insulin signaling: Insights into inflammation, oxidative stress, and endoplasmic reticulum stress - Yong Cheng; Junhao Wu; Yueqing Gao; Beijun Ang; Liduan Yin; Tong Wang; Qiuming Chen; Zhaojun Wang; Maomao Zeng; Jie Chen; Zhiyong He; Fengfeng Wu (Food Research International, 2025)

Integrated metabolomic and transcriptomic analysis reveals the regulatory effects of IAA on polyphenol biosynthesis and antioxidant activity in Phlebopus portentosus - Taobo Xiang; Feng Ge; Lei Zhu; Gaige Shao; Tao Wu; Hao Fan; Yueqian Liu; Longyu Wang; Jing Wang; Peng Li; Qin He; Ailiang Jiang; et al. (Food Bioscience, 2025)

Generation and resource potential of waste PV modules considering technological iteration: A case study in China - Zishuo Wang; Bo Li; Xiaolong Song; Xuning Zhuang; Wenjie Wu; Ang Li (Environmental Impact Assessment Review, 2025)

Balls-on-ball structured S-scheme heterojunction with localized hotspot effects for boosted photothermal-assisted photocatalytic synthesis of hydrogen - Yu Shen; Jinqi Shi; Jieyu Lei; Pengnian Shan; Ang Bian; Wei Kong; Arkadii Proskurin; Mengtian Wu; Changyu Lu; Guangzhao Wang; Weilong Shi (Chemical Engineering Journal, 2025)

Stratified charge assisted jet ignition mode (SCAJI) for low-speed two-stroke Otto cycle ammonia marine engine - Zhuohang Li; Yezeng Fan; Jinze Li; Kaijian Wu; Zhenyingnan Zhang; Fei Ren; Zhan Gao; Ang Li; Lei Zhu; Zhen Huang (Fuel, 2025)

Optimizing Fe in Mn-based Prussian blue analogs with dual redox-active sites to enhance operating voltage and durability in Zn-ion batteries - Hao Fu; Xianpeng Wang; Lingqian Ye; Zhiqiang Wu; Jun Yang; Minjie Shi; Edison Huixiang Ang (Chemical Engineering Journal, 2025)

Advanced membrane contactor coupled with electrodialysis metathesis for efficient carbon dioxide capture and waste salt remediation - Yundi Dong; Yangbo Qiu; Haili Wei; Chunhong Liu; Ke Wu; Junbin Liao; Edison Huixiang Ang; Jiangnan Shen (Desalination, 2024)

Disturbed glucose homeostasis and its increased allostatic load in response to individual, joint and fluctuating air pollutants exposure: Evidence from a longitudinal study in prediabetes - Yayuan Mei; Ang Li; Jiaxin Zhao; Yanbing Li; Quan Zhou; Ming Yang; Meiduo Zhao; Jing Xu; Kai Li; Guohuan Yin; Jingtao Wu; Qun Xu (Science of The Total Environment, 2024)

Formation mechanism and geophysical properties of fracture-filling gas hydrate in the host sediments: A comprehensive review - Gaowei Hu; Zhun Zhang; Yapeng Zhao; Qingtao Bu; Ang Li; Wengao Zhao; Zihao Wang; Xiaoqian Qiu; Tong Liu; Shengbiao Liu; Wanjun Lu; Nengyou Wu (Earth-Science Reviews, 2024)

Highly textured CMOS-compatible hexagonal boron nitride-based neuristor for reservoir computing - Haizhong Zhang; Jiayi Li; Xin Ju; Jie Jiang; Jing Wu; Dongzhi Chi; Diing Shenp Ang; Wei Hu; Rongshan Wei; Minmin Zhu; Xiaoqiang Lu (Chemical Engineering Journal, 2024)

Janus-structured colorimetric and fluorescent nanocomposites with highly luminescent retention to enhance point-of-care diagnosis - Xuan-ang Shen; Xirui Chen; Haoxiang Zhou; Song Chen; Jinyu Wu; Xiangmin Li; Xiaolin Huang; Yonghua Xiong (Chemical Engineering Journal, 2024)

Exceptional thermoelectric and mechanical performance in (Bi, Sb)2Te3 matrix facilitated by AgInSe2 alloying - Ruiheng Li; Wenxin Ou; Jianglong Zhu; Qian Deng; Xiaobo Tan; Qi Zhao; Tianbo Lu; Shaojingya Gao; Huangshui Ma; Hao Wu; Qiang Sun; Ran Ang (Chemical Engineering Journal, 2024)

Association Between Metal Exposure and Mitochondrial DNA Parameters and the Potential Mediation Effect of Oxidative Stress - Jing Xu; Meiduo Zhao; Xiaoyu Ge; Xiaolin Liu; Lanping Wei; Ang Li; Yayuan Mei; Guohuan Yin; Jingtao Wu; Qun Xu (Exposure and Health, 2024)

Analysis of resting status reveals distinct elevational variation in metabolisms of lizards - Zhong‐Wen Jiang; Liang Ma; Shi‐ang Tao; Cheng Wenda; Chuyu Cheng; Dan‐yang Wu; Wei‐Guo Du (Ecology, 2024)
Animals spend a considerable proportion of their life span at rest. However, resting status has often been overlooked when investigating how species respond to environmental conditions. This may induce a large bias in understanding the local adaptation of species across environmental gradients and their vulnerability to potential environmental change. Here, we conducted an empirical study on montane agamid lizards, combined with mechanistic modeling, to compare elevational variations in body temperature and metabolisms (cumulative digestion and maintenance cost) between resting and active status. Our study on three populations of an agamid lizard along an elevational gradient revealed a trend of decreasing body temperature toward higher elevations, the main contributor of which was resting status of the lizards. Using population‐specific reaction norms, we predicted greater elevational variation in hourly and cumulative digestion for resting lizards than for active lizards. Climate‐change impacts, estimated as the change in cumulative digestion, also show greater elevational variation when resting status is factored into the analysis. Further, our global analysis of 98 agamid species revealed that in about half of their combined distributional range, the contribution of resting status in determining the elevational variation in cumulative digestion and maintenance cost of lizards was greater than the contribution made by a lizard's active status. Our study highlights the importance of considering resting status when investigating how species respond to environmental conditions, especially for those distributed over tropical and subtropical mountain areas.

Marine microplastics enhance release of arsenic in coastal aquifer during seawater intrusion process - Chengpeng Yuan; Liyang Hu; Zhefan Ren; Xiaoyun Xu; Xiangyang Gui; Xuan-ang Gong; Rui Wu; Jingke Sima; Xinde Cao (Journal of Hazardous Materials, 2024)

Non-sacrificial additive regulated electrode–electrolyte interface enables long-life, deeply rechargeable aqueous Zn anodes - Ang Li; Xinyu Zhang; Zeyu Xu; Maochun Wu (Chemical Engineering Journal, 2024)

Mo4/3B2Tx induced hierarchical structure and rapid reaction dynamics in MoS2 anode for superior sodium storage - Guilong Liu; Wenzhuo Yuan; Zihan Zhao; Jin Li; Naiteng Wu; Donglei Guo; Xiao Liu; Yong Liu; Ang Cao; Xianming Liu (Chemical Engineering Journal, 2024)

Low-temperature hydrogen production from waste polyethylene by nonthermal plasma (NTP)-assisted catalytic pyrolysis using NiCeOx/β catalyst - Jiaxing Song; Jiabao lv; Yuhan Pan; Jingyu Wang; Jun Wang; Ang Cao; Angjian Wu; Paul T. Williams; Qunxing Huang (Chemical Engineering Journal, 2024)

Leaching behaviors of dissolved organic matter from face masks revealed by fluorescence EEM combined with FRI and PARAFAC - Zhong Jin; Weibo Zhang; Xihuan Wang; Ang Liu; Zhongyu Li; Yingchen Bai; Fengchang Wu (Water Research, 2024)

Lateral migration of methane at a cold seep: Evidence from U–Th dating of methane-derived authigenic carbonate in the Middle Okinawa Trough - Ang Li; Nengyou Wu; Zhifeng Wan; Qing Li; Zhilei Sun; Feng Cai; Dong Feng (Marine and Petroleum Geology, 2024)

Harnessing interfacial π–d conjugation in covalently linked COFs with amine-Zn0.4Cd0.6S strengthens photoinduced charge transfer for photocatalysis - Chencheng Qin; Yi Yang; Guoxi Zhou; Edison Huixiang Ang; Hou Wang; Yan Wu (Chemical Engineering Journal, 2024)

Illegal synthetic dyes in spices: a Singapore case study - Zan Xin Chin; Sew Lay Chua; Yi Li Ang; Sheena Wee; Ken Kah Meng Lee; Yuansheng Wu; Joanne Sheot Harn Chan (Food Additives & Contaminants Part B-Surveillance, 2024)

Enhancing physicochemical, antimicrobial, and release properties of fish skin gelatin films using dual-layer nanoparticles loaded with tea polyphenols/kojic acid for air-dried chicken preservation - Ang Zhang; Xiankang Fan; Xiaoqun Zeng; Jue Xu; Changyu Zhou; Qiang Xia; Yangying Sun; Zhen Wu; Daodong Pan (Food Hydrocolloids, 2024)

Mechanism analysis of promoting calcium absorption and bone formation of peptides from different casein fractions - Chenhui Lei; Xiaomeng Wu; Shengyuan Wang; Ang Gao; Guangqing Mu; Fang Qian (Food Bioscience, 2024)

On-demand detachable adhesive hydrogel based on dual dynamic covalent cross-linked with NIR/pH dual-responsive properties for diabetic wound healing - Kaize Su; Duanyu Deng; Xiaoxian Wu; Yumu Song; Ying Sun; Xu Wang; Zhen Zhang; Jinxuan Li; Zhenping Yan; Xiangcun Shang; Chen Li; Kun Zhang; et al. (Chemical Engineering Journal, 2024)

Hirsutinolide-type sesquiterpenoids with anti-prostate cancer activity from Cyanthillium cinereum - Song Ang; Chun Liu; Peng Hong; Lei Yang; Gui'e Hu; Xi Zheng; Jingwei Jin; Rihui Wu; Wing-Leung Wong; Kun Zhang; Lishe Gan; Dongli Li (Phytochemistry, 2023)

Investigation of filtration performance and phosphorus removal in an electric field controlled dynamic membrane bioreactor - Long Chen; Miao Lv; Yang-Cheng Ding; Zi-Ang Lv; Dan-Na Ding; Di Wu; Haiping Yuan; Nanwen Zhu; Hua-Jun Feng (Chemical Engineering Journal, 2023)

Effects of Environmental Heavy Metal Interactions on Renal Impairment: Epidemiological Evidence from Rural Northeastern China - Guohuan Yin; Xiaoyu Ge; Meiduo Zhao; Jing Xu; Ang Li; Yayuan Mei; Jingtao Wu; Xiaolin Liu; Lanping Wei; Qun Xu (Exposure and Health, 2023)

Fractional model for simulating Long-Term fracture conductivity decay of shale gas and its influences on the well production - Yu Peng; Ang Luo; Yongming Li; Yijia Wu; Wenjun Xu; Kamy Sepehrnoori (Fuel, 2023)

Prospects and perspectives on advanced materials for sodium-ion batteries - Zhen-Yi Gu; Xiao-Tong Wang; Yong-Li Heng; Kai-Yang Zhang; Hao-Jie Liang; Jia-Lin Yang; Edison Huixiang Ang; Peng-Fei Wang; Ya You; Fei Du; Xing-Long Wu (Science Bulletin, 2023)

A new insight into the CaO-induced inhibition pathways on PCDD/F formation: Metal passivation, dechlorination and hydroxide substitution - Xiaoxiao Wang; Jiabao Lv; Yuxuan Ying; Yunfeng Ma; Angjian Wu; Xiaoqing Lin; Ang Cao; Xiaodong Li; Jianhua Yan (Science of The Total Environment, 2023)

Combined toxic effects of nanoplastics and norfloxacin on mussel: Leveraging biochemical parameters and gut microbiota - Ran Xu; Li'ang Li; Jiahui Zheng; Chenglong Ji; Huifeng Wu; Xiang Chen; Yuchuan Chen; Menghong Hu; Elvis Genbo Xu; Youji Wang (Science of The Total Environment, 2023)

Pulses outweigh cumulative effects of water diversion from river to lake on lacustrine phytoplankton communities - Jiangyu Dai; Haifei Sha; Xiufeng Wu; Shiqiang Wu; Yu Zhang; Fangfang Wang; Ang Gao; Jiayi Xu; Fuwei Tian; Senlin Zhu; Mariusz Ptak (Environmental Geochemistry and Health, 2023)

Novel caffeic acid grafted chitosan-sodium alginate microcapsules generated by microfluidic technique for the encapsulation of bioactive peptides from silkworm pupae - Xiao-Meng Xun; Zhi-Ang Zhang; Zi-Xuan Yuan; Kamila Tuhong; Cheng-Hai Yan; Yu-Fan Zhan; Guo-Ping Kang; Qiong-Ying Wu; Jun Wang (Sustainable Chemistry and Pharmacy, 2023)

scRNA-seq analysis reveals toxicity mechanisms in shrimp hemocytes subjected to nitrite stress - QingJian Liang; BeiBei Dong; Ang Li; LiTing Wu; Yu Zhang; Tao Han; Xing Liu (Chemosphere, 2023)

Comparison of alive and dead benthic foraminiferal fauna off the Changjiang Estuary: Understanding water-mass properties and taphonomic processes - Feng Jiang; Daidu Fan; Quanhong Zhao; Yijing Wu; Fahui Ren; Yan Liu; Ang Li (Frontiers in Marine Science, 2023)
Benthic foraminifera (BF) are utilized in palaeo-environmental reconstruction based on our understanding of how living individuals respond to environmental variations. However, there is still a lack of empirical insight into how non-environmental factors, such as taphonomic processes, influence the preservations of fossil BF in strata. In this study, we compare the spatial distribution and composition of alive and dead BF fauna in surface sediments to elucidate how well fossil foraminiferal fauna mirror quasi-contemporary alive BF groups indicative of different water masses off a mega-river (Changjiang) estuary, which is characterized by intense and complex river-sea interactions. On-site measurements of bottom water salinity, temperature, and dissolved oxygen were conducted in the summer to determine water mass properties. A same-site comparison of alive (Rose Bengal stained) and dead foraminiferal fauna in surface sediment samples over 73 stations was then carried out. Q-mode Hierarchical clustering analysis was used to differentiate foraminiferal assemblages based on the relative abundance of common species. Three distinct regions with different water-mass properties were identified. The distribution pattern of dead foraminiferal fauna is mainly inherited from alive fauna, while the density and diversity of the dead fauna were found to be higher than those of the alive one. Both alive and dead fauna were clustered into four assemblages. A few common alive species (small-agglutinated and thin-calcareous) were rarely found in dead fauna, and a few common dead species (preferring low temperature and indicating allochthonous sources) were rarely present in alive fauna. The alive foraminiferal abundance and diversity were mainly determined by food resources and environmental properties of salinity and temperature. Alive foraminiferal assemblages were separated by different water masses determined by river-sea interactions off the Changjiang Estuary. The “time-averaging” effect was found to be responsible for the higher density and diversity of the dead fauna. Disintegration of agglutinated tests, dissolution of calcareous tests and selective transportation were observed to contribute to the different species compositions between the alive and dead fauna. Nevertheless, indicative species-environment relations in alive and taphocoenose fauna were found to be almost homologous among most common species. This suggests that distinct benthic foraminiferal assemblages can be used to effectively differentiate between different water masses in the study coastal seas.

Dual RNA-seq reveals a host-pathogen interaction transcriptional regulation pattern between Cryptocaryon irritans and large yellow croaker (Larimichthys crocea) - Yulin Bai; Yue Liu; Ang Qu; Jiaying Wang; Ji Zhao; Qiaozhen Ke; Xintong Chen; Fei Pu; Linni Wu; Peng Xu; Tao Zhou (Aquaculture, 2023)

Identification and Expression Analysis of LncRNAs Reveal the Immune Mechanism of Visceral White-Nodules Disease Resistance in Large Yellow Croaker - Yulin Bai; Xintong Chen; Ang Qu; Yue Liu; Ji Zhao; Qiaozhen Ke; Fei Pu; Linni Wu; Hongshu Chi; Hui Gong; Tao Zhou; Peng Xu (Marine Biotechnology, 2023)

Seasonal drivers of productivity and calcification in the coral Platygyra carnosa in a subtropical reef - Walter Dellisanti; Jeffery T. H. Chung; Sam K. F. Yiu; Ryan Ho Leung Tsang; Put Ang; Yip Hung Yeung; Jian-Wen Qiu; Shelby E. McIlroy; Mark L. Wells; Jiajun Wu; Leo Lei Chan (Frontiers in Marine Science, 2023)
Scleractinian corals are increasingly subjected to local stressors combined with global changes. In subtropical areas, corals exhibit metabolic plasticity and resilience in response to variability and extremes in local temperature, salinity, and light; however, the physiological mechanisms by which corals acclimate or adapt to these changing conditions remain disputed. We assessed the physiological status of the coral Platygyra carnosa during a two-year in situ monitoring survey. To obtain metabolic rates (respiration and photosynthesis), photochemical efficiency (Fv / Fm), and biocalcification measurements, non-invasive techniques such as underwater respirometry, Pulse Amplitude Modulated (PAM) fluorometry, total alkalinity measurements, and digital photography were used. Our findings show clear seasonality in water quality parameters, which affected coral health. Elevated temperatures during the summer were below the maximum monthly mean < 31°C) but reduced the energetic productivity of corals (-44% relative to winter). Fluctuations in salinity (25–38 ppt) and pH (7.65–8.44) were linked to rainfall and reduced calcification rates. The conditions during the spring were favorable for coral metabolism and calcification (+20% relative to summer). Overall, our research demonstrates that the metabolic plasticity of P. carnosa in response to shifts in seawater quality allows this species to survive ongoing environmental change. Our in situ observations provide fundamental insights into coral response mechanisms under changing environmental conditions and contribute to projections of coral health under future scenarios of global change.

Green development strategy of offshore wind farm in China guided by life cycle assessment - Jingjing Chen; Bingjing Mao; Yufeng Wu; Dongya Zhang; Yiqun Wei; Ang Yu; Lihong Peng (Resources, Conservation and Recycling, 2023)

Advanced layered oxide cathodes for sodium/potassium-ion batteries: Development, challenges and prospects - Zhi-Xiong Huang; Zhen-Yi Gu; Yong-Li Heng; Edison Huixiang Ang; Hong-Bo Geng; Xing-Long Wu (Chemical Engineering Journal, 2023)

Microfluidic preparation of a novel phoxim nanoemulsion pesticide against Spodoptera litura - Zong-Nan Li; Yu-Xuan Zhang; Zhi-Ang Zhang; Lian-Han Pan; Ping Li; Yan Xu; Sheng Sheng; Fu-An Wu; Jun Wang (Environmental Science and Pollution Research, 2022)

Tissue-Specific Analysis of Alternative Splicing Events and Differential Isoform Expression in Large Yellow Croaker (Larimichthys crocea) After Cryptocaryon irritans Infection - Ang Qu; Yulin Bai; Xinyi Zhang; Junjia Zeng; Fei Pu; Linni Wu; Peng Xu; Tao Zhou (Marine Biotechnology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Effect of confining pressure on peak penetration force of the TBM disc cutter - Wu Li; Peng Yan; Ang Lu; Shuling Huang; Wenbo Lu (Arabian Journal of Geosciences, 2022)

FOXA2 inhibits doxorubicin-induced apoptosis via transcriptionally activating HBP rate-limiting enzyme GFPT1 in HCC cells - Huang Huang; Yuhan Wang; Tianmiao Huang; Lingyan Wang; Yangzhi Liu; Qiong Wu; Ang Yu; Meiyun Shi; Xiaoyu Wang; Wenli Li; Jianing Zhang; Yubo Liu (Journal of Physiology and Biochemistry, 2021)

Small–Scale Experimental Investigation of Fatigue Performance Improvement of Ship Hatch Corner with Shot Peening Treatments by Considering Residual Stress Relaxation - Jin Gan; Zi’ang Gao; Yiwen Wang; Zhou Wang; Weiguo Wu (Journal of Marine Science and Engineering, 2021)
Ship hatch corner is a common structure in a ship and its fatigue problem has always been one of the focuses in ship engineering due to the long–term high–stress concentration state during the ship’s life. For investigating the fatigue life improvement of the ship hatch corner under different shot peening (SP) treatments, a series of fatigue tests, residual stress and surface topography measurements were conducted for SP specimens. Furthermore, the distributions of the surface residual stress are measured with varying numbers of cyclic loads, investigating the residual stress relaxation during cyclic loading. The results show that no matter which SP process parameters are used, the fatigue lives of the shot–peened ship hatch corner specimens are longer than those at unpeened specimens. The relaxation rate of the residual stress mainly depends on the maximum compressive residual stress (σRSmax) and the depth of the maximum compressive residual stress (δmax). The larger the values of σRSmax and δmax, the slower the relaxation rates of the residual stress field. The results imply that the effect of residual stress field and surface roughness should be considered comprehensively to improve the fatigue life of the ship hatch corner with SP treatment. The increase in peening intensity (PI) within a certain range can increase the depth of the compressive residual stress field (CRSF), so the fatigue performance of the ship hatch corner is improved. Once the PI exceeds a certain value, the surface damage caused by the increase in surface roughness will not be offset by the CRSF and the fatigue life cannot be improved optimally. This research provides an approach of fatigue performance enhancement for ship hatch corners in engineering application.

A Diver-Portable Respirometry System for in-situ Short-Term Measurements of Coral Metabolic Health and Rates of Calcification - Walter Dellisanti; Ryan H. L. Tsang; Put Ang; Jiajun Wu; Mark L. Wells; Leo L. Chan (Frontiers in Marine Science, 2020)

Effect of Bedding Angle and Mineral Composition on Mechanical Properties and Fracture Behavior of Phyllite Under Unloading Confining Pressures - Xiaolong Guo; Zhongsheng Tan; Xiao Wang; Ang Li; Zhongjun Ma; Yongsheng Wu (Geotechnical and Geological Engineering, 2020)

Proteomics analysis of Schwann cell-derived exosomes: a novel therapeutic strategy for central nervous system injury - Zhijian Wei; Baoyou Fan; Han Ding; Yang Liu; Haoshuai Tang; Dayu Pan; Jiaxiao Shi; Pengyuan Zheng; Hongyu Shi; Heng Wu; Ang Li; Shiqing Feng (Molecular and Cellular Biochemistry, 2019)

Strain identification and metabolites isolation of Aspergillus capensis CanS-34A from Brassica napus - Jing Qin; Ang Lyu; Qing-hua Zhang; Long Yang; Jing Zhang; Ming-de Wu; Guo-qing Li (Molecular Biology Reports, 2019)

Exploring Local Perceptions of and Attitudes toward Endangered François’ Langurs (Trachypithecus francoisi) in a Human-Modified Habitat - Kefeng Niu; Wei Liu; Zhi Xiao; Ankang Wu; Tianyou Yang; Isidoro Riondato; Amanda L. Ellwanger; Andie Ang; Marco Gamba; Yeqin Yang; Cristina Giacoma (International Journal of Primatology, 2019)

Two hybrid data-driven models for modeling water-air temperature relationship in rivers - Senlin Zhu; Marijana Hadzima-Nyarko; Ang Gao; Fangfang Wang; Jingxiu Wu; Shiqiang Wu (Environmental Science and Pollution Research, 2019)

Transgenic Mice Overexpressing the Divalent Metal Transporter 1 Exhibit Iron Accumulation and Enhanced Parkin Expression in the Brain - Cheng-Wu Zhang; Yee Kit Tai; Bing-Han Chai; Katherine C. M. Chew; Eng-Tat Ang; Fai Tsang; Bryce W. Q. Tan; Eugenia T. E. Hong; Abu Bakar Ali Asad; Kai-Hsiang Chuang; Kah-Leong Lim; Tuck Wah Soong (NeuroMolecular Medicine, 2017)

Ethylene promotes mycelial growth and ganoderic acid biosynthesis in Ganoderma lucidum - Guang Zhang; Ang Ren; Fengli Wu; Hanshou Yu; Liang Shi; Mingwen Zhao (Biotechnology Letters, 2017)

Scutellarin as a Potential Therapeutic Agent for Microglia-Mediated Neuroinflammation in Cerebral Ischemia - Yun Yuan; Ming Fang; Chun-Yun Wu; Eng-Ang Ling (NeuroMolecular Medicine, 2016)

Alterations and correlations of the gut microbiome, metabolism and immunity in patients with primary biliary cirrhosis - Long‐Xian Lv; Dai‐Qiong Fang; Ding Shi; De‐Ying Chen; Ren Yan; Yi‐Xin Zhu; Yan‐Fei Chen; Li Shao; Fei‐Fei Guo; Wen‐Rui Wu; Ang Li; Hai‐Yan Shi; et al. (Environmental Microbiology, 2016)
Summary We selected 42 early‐stage primary biliary cirrhosis (PBC) patients and 30 healthy controls (HC). Metagenomic sequencing of the 16S rRNA gene was used to characterize the fecal microbiome. UPLC‐MS/MS assaying of small molecules was used to characterize the metabolomes of the serum, urine and feces. Liquid chip assaying of serum cytokines was used to characterize the immune profiles. The gut of PBC patients were depleted of some potentially beneficial bacteria, such as Acidobacteria, Lachnobacterium sp., Bacteroides eggerthii and Ruminococcus bromii , but were enriched in some bacterial taxa containing opportunistic pathogens, such as γ‐Proteobacteria, Enterobacteriaceae, Neisseriaceae, Spirochaetaceae , Veillonella , Streptococcus , Klebsiella , Actinobacillus pleuropneumoniae , Anaeroglobus geminatus , Enterobacter asburiae , Haemophilus parainfluenzae , Megasphaera micronuciformis and Paraprevotella clara . Several altered gut bacterial taxa exhibited potential interactions with PBC through their associations with altered metabolism, immunity and liver function indicators, such as those of Klebsiella with IL‐2A and Neisseriaceae with urinary indoleacrylate. Many gut bacteria, such as some members of Bacteroides, were altered in their associations with the immunity and metabolism of PBC patients, although their relative abundances were unchanged. Consequently, the gut microbiome is altered and may be critical for the onset or development of PBC by interacting with metabolism and immunity.

Analysis of the sucrose synthase gene family in tobacco: structure, phylogeny, and expression patterns - Zhong Wang; Pan Wei; Mingzhu Wu; Yalong Xu; Feng Li; Zhaopeng Luo; Jianfeng Zhang; Ang Chen; Xiaodong Xie; Peijian Cao; Fucheng Lin; Jun Yang (Planta, 2015)

The bacterial lipopeptide iturins induce V erticillium dahliae cell death by affecting fungal signalling pathways and mediate plant defence responses involved in pathogen‐associated molecular pattern‐triggered immunity - Qin Han; Fengli Wu; Xiaonan Wang; Hong Qi; Liang Shi; Ang Ren; Qinghai Liu; Mingwen Zhao; Canming Tang (Environmental Microbiology, 2015)
Summary V erticillium wilt in cotton caused by V erticillium dahliae is one of the most serious plant diseases worldwide. Because no known fungicides or cotton cultivars provide sufficient protection against this pathogen, V . dahliae causes major crop yield losses. Here, an isolated cotton endophytic bacterium, designated B acillus amyloliquefaciens 41 B ‐1, exhibited greater than 50% biocontrol efficacy against V . dahliae in cotton plants under greenhouse conditions. Through high‐performance liquid chromatography and mass analysis of the filtrate, we found that the antifungal compounds present in the strain 41 B ‐1 culture filtrate were a series of isoforms of iturins. The purified iturins suppressed V . dahliae microsclerotial germination in the absence or presence of cotton. Treatment with the iturins induced reactive oxygen species bursts, H og1 mitogen‐activated protein kinase (MAPK) activation and defects in cell wall integrity. The oxidative stress response and high‐osmolarity glycerol pathway contribute to iturins resistance in V . dahliae . In contrast, the S lt2 MAPK pathway may be involved in iturins sensitivity in this fungus. In addition to antagonism, iturins could induce plant defence responses as activators and mediate pathogen‐associated molecular pattern‐triggered immunity. These findings suggest that iturins may affect fungal signalling pathways and mediate plant defence responses against V . dahliae .

Identification of fucans from four species of sea cucumber by high temperature 1H NMR - Nian Wu; Shiguo Chen; Xingqian Ye; Guoyun Li; Li’ang Yin; Changhu Xue (Journal of Ocean University of China, 2014)

Purification, molecular cloning, and antimicrobial activity of peptides from the skin secretion of the black-spotted frog, Rana nigromaculata - Ang Li; Yong Zhang; Che Wang; Geng Wu; Zhenchun Wang (World Journal of Microbiology and Biotechnology, 2013)

Boron distribution and mobility in navel orange grafted on citrange and trifoliate orange - Gui-Dong Liu; Rui-Dong Wang; Li-Shu Wu; Shu-Ang Peng; Yun-Hua Wang; Cun-Cang Jiang (Plant and Soil, 2012)

Seismic fragility analysis of highway bridges considering multi-dimensional performance limit state - Qi’ang Wang; Ziyan Wu; Shukui Liu (Earthquake Engineering and Engineering Vibration, 2012)

Diversity‐dependent stability under mowing and nutrient addition: evidence from a 7‐year grassland experiment - Haijun Yang; Lin Jiang; Linghao Li; Ang Li; Mingyu Wu; Shiqiang Wan (Ecology Letters, 2012)
Ecology Letters (2012) Abstract Anthropogenic perturbations may affect biodiversity and ecological stability as well as their relationships. However, diversity–stability patterns and associated mechanisms under human disturbances have rarely been explored. We conducted a 7‐year field experiment examining the effects of mowing and nutrient addition on the diversity and temporal stability of herbaceous plant communities in a temperate steppe in northern China. Mowing increased population and community stability, whereas nutrient addition had the opposite effects. Stability exhibited positive relationships with species richness at population, functional group and community levels. Treatments did not alter these positive diversity–stability relationships, which were associated with the stabilising effect of species richness on component populations, species asynchrony and portfolio effects. Despite the difficulty of pinpointing causal mechanisms of diversity–stability patterns observed in nature, our results suggest that diversity may still be a useful predictor of the stability of ecosystems confronted with anthropogenic disturbances.

Biosorption of di(2-ethylhexyl)phthalate by seaweed biomass - H.W. Chan; T.C. Lau; P.O. Ang; M. Wu; P.K. Wong (Journal of Applied Phycology, 2004)